2017
DOI: 10.1021/acs.energyfuels.7b02855
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of n-Butylbenzene at Various Pressures: Influence of Long Side-Chain Structure on Alkylbenzene Pyrolysis

Abstract: This work investigates the pyrolysis of n-butylbenzene, which widely exists in transportation fuels and their surrogate mixtures. Both reactive and stable pyrolysis products were comprehensively detected with synchrotron vacuum ultraviolet photoionization mass spectrometry. Their mole fractions versus temperature were also evaluated at 30, 150, and 760 Torr. A kinetic model of n-butylbenzene pyrolysis was developed, and new data were used to validate the model. On the basis of the modeling analysis, the benzyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 50 publications
3
21
1
Order By: Relevance
“…As a result, tetralin is almost totally consumed by bimolecular reactions via the attack of small radicals, while the unimolecular decomposition reactions show only minor contributions to the consumption of tetralin in both the lean and rich flames. This is similar to the case in the pyrolysis of tetralin, 14 which indicates that tetralin has quite different decomposition characteristics to alkylbenzenes like ethylbenzene, 29,40 n ‐propylbenzene, 33,41 and n ‐butylbenzene 42,43 . Among the unimolecular decomposition reactions, the H 2 ‐elimination reaction producing H2A2 and H 2 and the simultaneous cleavage of two benzylic CC bonds producing o ‐xylylene (o‐C 8 H 8 ) and C 2 H 4 are the dominant ones in both the lean and rich flames, while the total contribution of unimolecular decomposition reactions to the consumption of tetralin is enhanced in the rich flame, as shown in Figure 5.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…As a result, tetralin is almost totally consumed by bimolecular reactions via the attack of small radicals, while the unimolecular decomposition reactions show only minor contributions to the consumption of tetralin in both the lean and rich flames. This is similar to the case in the pyrolysis of tetralin, 14 which indicates that tetralin has quite different decomposition characteristics to alkylbenzenes like ethylbenzene, 29,40 n ‐propylbenzene, 33,41 and n ‐butylbenzene 42,43 . Among the unimolecular decomposition reactions, the H 2 ‐elimination reaction producing H2A2 and H 2 and the simultaneous cleavage of two benzylic CC bonds producing o ‐xylylene (o‐C 8 H 8 ) and C 2 H 4 are the dominant ones in both the lean and rich flames, while the total contribution of unimolecular decomposition reactions to the consumption of tetralin is enhanced in the rich flame, as shown in Figure 5.…”
Section: Resultssupporting
confidence: 69%
“…This is similar to the case in the pyrolysis of tetralin, 14 which indicates that tetralin has quite different decomposition characteristics to alkylbenzenes like ethylbenzene, 29,40 n-propylbenzene, 33,41 and n-butylbenzene. 42,43 Among the unimolecular decomposition reactions, the H 2 -elimination reaction producing H2A2 and H 2 and the simultaneous cleavage of two benzylic C C bonds producing o-xylylene (o-C 8 H 8 ) and C 2 H 4 are the dominant ones in both the lean and rich flames, while the total contribution of unimolecular decomposition reactions to the consumption of tetralin is enhanced in the rich flame, as shown in Figure 5. It can be found that both of the two dominant unimolecular decomposition reactions are not producing any radicals, indicating the negligible roles of the unimolecular decomposition reactions in the chain reaction system of tetralin flames.…”
Section: Fuel Decomposition and Smaller Products Formationmentioning
confidence: 99%
“…The present work first investigated the temperature, pressure and reaction time dependencies of the yields of CH4, C6H6 and C7H8, based on detailed kinetic models [23][24][25]. Three C10 fuels, n-decane, decalin and n-butylbenzene, were selected to represent paraffinic, naphthenic and aromatic fuel classes.…”
Section: Ch4 and The Ratio Of [C6h6]/([c6h6]+[c7h8]mentioning
confidence: 99%
“…were initially collected from experiments on the pyrolysis of 44 neat fuels, covering wide temperature, pressure and reaction time conditions. They were obtained in different labs with various experimental apparatus, such as shock tubes [26][27][28][29], flow reactors [22,25,30,31] and jet-stirred reactors (JSR) [32,33]. All of these collected speciation data included experimental uncertainties, so they were evaluated to establish consistency across different datasets.…”
Section: Ch4 and The Ratio Of [C6h6]/([c6h6]+[c7h8]mentioning
confidence: 99%
“…The flow reactor pyrolysis experiments were performed at the National Synchrotron Radiation Laboratory. Detailed introduction to the beamline and the flow reactor apparatus have been introduced elsewhere [16][17][18][19]. o-Xylene (purchased from Sinopharm Chemical Reagent Limited Co., Shanghai, China, with purity≥99%) was gasified in a home-made vaporizer.…”
Section: Flow Reactor Pyrolysismentioning
confidence: 99%